Análisis de las preferencias de financiamiento por parte de las organizaciones de la economía popular y solidaria de la provincia del Azuay inscritas en el registro único de actores de la economía popular y solidaria, en el período 2019-2021 - Ochoa Rosales, Hugo Eloy (2022)
The purpose of this study is to analyze the sources of financing of the organizations of the popular and solidarity economy (EPS) of the province of Azuay, registered in the single registry of actors of the popular and solidarity economy (RUEPS), in the period 2019 -2021. The methodological approach is based on the quantitative approach with an exploratory and descriptive scope, through which, through the application of surveys to 76 organizations, information was obtained related to the preferred sources of financing, and the main motivations for selecting said sources. The results showed that popular and solidarity finance organizations are the preferred source of financing, although a significant number of organizations never accessed financing for different reasons that are analyzed in the results presentation section. Finally, general guidelines are proposed for the design of financial products and services according to the needs of EPS organizations.